Immunological studies of psoriatic arthritis - Zipperlen, Katrin. (2008)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2008. Medicine Includes bibliographical references (leaves 136-141) Since little is known about the contribution of B cells to the pathology of psoriatic arthritis (PsA), this study investigated the possible recruitment of peripheral blood B cells to sites of inflammation by differential expression of chemokine receptors CXCR3, CXCR4, CXCR5, CCR1, CCR2, CCR5 and CCR6. Secondly, we explored the role of B cell activating factor (BAFF) in PsA. The chemokine receptor expression analysis did not reveal any significant differences (p-values >0.05 for all receptors) both at the RNA and the protein level when comparing PsA patients (n = 13) to rheumatoid arthritis (RA) patients (n = 15) and healthy controls (n = 10). Also, there was no significant difference (p = 0.1291) in plasma BAFF levels between PsA (n = 37) or RA patients (n = 24) and healthy controls (n = 35). Our study does not provide supporting evidence of B cell involvement in PsA, however it was limited to the analysis of peripheral blood.